Risolvere senza la tecnica x sostituzione.
Dapprima l'indefinito
$\int \frac{e^{2x}-e^x}{e^x+1} \, dx =$
$\int e^x\frac{e^x-1}{e^x+1} \, dx =$
$=\int e^x \cdot \frac{e^x+1}{e^x+1} - 2\frac{e^x}{e^x+1} \, dx =$
Integrale immediato
$=\int e^x\frac{e^x+1}{e^x+1} \, dx - 2ln(e^x+1) =$
$=\int e^x \, dx - 2ln(e^x+1) =$
$=e^x - 2ln(e^x+1) + c $
passiamo al definito
$\int_0^{ln2} \frac{e^{2x}-e^x}{e^x+1} \, dx =$
$= \left. e^x - 2ln(e^x+1) \right|_0^{ln2} =$
$ = 2-2ln(3) -1 + 2 ln(2) =$
$ = 1 - 2ln\left( \frac{3}{2} \right) $